Cree Peoplehood, International Trade, and Diplomacy - Jobin, Shalene (Revue générale de droit, 2013)
Self-determination for Indigenous peoples in settler-colonial countries like Canada is an ongoing process where Indigenous peoples simultaneously focus externally to create expanded jurisdictional space while also re-establishing their own governing processes. Canadian economic progress has come at a cost to Indigenous peoples, undermining their collective rights to economic security and self-determination. In this article, I explore Cree peoplehood as a way to conceive Cree nationhood as distinct from conceptions of the nation-State. I rely significantly on archival sources to explore how the Cree were, and were also seen as, a self-determining people. After exploring the internal aspects of Cree peoplehood, I then examine the external relations of the Cree: focusing on inter-nation trade, trade networks, transportation, and a trade language as nations engage in trade and diplomacy, as one method to exercise their authority and jurisdiction. The final section investigates the diplomatic relations of the Plains Cree. This article is adding to the peoplehood literature by not only applying this concept to domestic relations but also examining foreign relations. It also adds to the writing on Cree self-determination by exploring how historic relationships and practices can inform current self-determination aspirations. This type of research can substantiate and provide historical analyses of Indigenous nationhood to further understand the context behind current economic and political self-determination movements.